1979
DOI: 10.1128/jb.137.3.1158-1164.1979
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lysostaphin endopeptidase production and cell wall composition in Staphylococcus staphylolyticus

Abstract: Mutants of Staphylococcus staphylolyticus incapable of producing an extracellular staphylolytic glycylglycine endopeptidase were isolated and found to have cells in the population susceptible to lysis by this enzyme, as did the wild-type organism under conditions in which the endopeptidase was not produced. These results suggest that cultures of this organism normally contain a heterogeneous population of cells with regard to cell wall composition and susceptibility to the enzyme. Production of the endopeptida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Lysostaphin is an endopeptidase produced in other Staphylococci spp. that hydrolyzes the peptide cross bridges between PG strands (47, 48). We found that Δ ltaA and Δ ugtP mutants were substantially more susceptible to these enzymes than were wild type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lysostaphin is an endopeptidase produced in other Staphylococci spp. that hydrolyzes the peptide cross bridges between PG strands (47, 48). We found that Δ ltaA and Δ ugtP mutants were substantially more susceptible to these enzymes than were wild type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ml of a clear agar underlay (1.5 g of Bacto agar per 100 ml of deionized water). Figure 1 shows that spontaneous or N-methyl-N'-nitro-Nnitrosoguanidine-induced variants of S. staphylolyticus (10) with different eyoenzyme-producing capabilities can be identified easily with the screening medium. The wild-type organism produced all three exoenzymes and, therefore, had a clear zone of cell lysis and casein hydrolysis surrounding each colony (Fig.…”
Section: Figmentioning
confidence: 99%
“…A variant that had a slightly turbid zone around each colony (Fig. 1B) was found on subsequent assay of culture supernatant (10,11) to have lost the ability to produce active endopeptidase, although it still produced active protease and hexosaminidase. These additional assays were required to identify the specific enzyme defect, because the medium did not allow a differentiation among the three types of single mutants.…”
Section: Figmentioning
confidence: 99%
“…Mother S. simulans is also resistant against lysostaphin due to the production of immunity factor, incorporating the serine residues into the interpeptide bridges. It causes lysostaphin to be unable to hydrolyse Gly‐Ser or Ser‐Gly peptide bonds (Robinson et al. 1979; Heath et al.…”
Section: Introductionmentioning
confidence: 99%